TEKNIK PERBANYAKAN KIJIWO (EUCHRESTA HORSFIELDII (LESCH.) BENN.) MELALUI STEK PUCUK - Ekasari, Indriani (LIPI Press, 2011)
Kijiwo (Euchresta horsfi eldii (Lesch.) Benn.) is one of the Indonesia native species that had a habitat in montane forest. Propagation of Kijiwo through generative is very diffi cult to fi nd. The alternative conservation effort for Kijiwo is a shoot propagation. The aims of this study were to estimate the growth percentage of shoot propagation and to determine the effectiveness of artifi cial hormone for rooting on shoot propagation. The artifi cial hormone that be used were IAA, IBA, NAA, and Rootone F. Control treatment was also conducted as non treatment indicator. This study was conducted in the nursery of Cibodas Botanic Garden for 5 months. Randomized Complete Block Design with 2 blocks (potrays). Each potray contains 45 polytube for 45 shoot that can consist 5 artifi cial hormone treatments and each treatment were replicated into 9 shoots. Watering was done every 3 days and checking the root was done every month. Parameters of this study were root number, root length, wet weight of root, and dry weight of root. Data analyzed on R.2.12.2 software with two-way ANOVA. The result showed that growth percentage was 98,89%. The application on artifi cial hormone showed not signifi cant difference on parameters (P>0,05). Only block treatment on wet weight of root showed signifi cant different (P<0,05).